Effect of over expressing protective antigen on global gene transcription in Bacillus anthracis BH500. Issue 1 (December 2018) - Sharma, Ashish; Leppla, Stephen; Pomerantsev, Andrei; Shiloach, Joseph
Abstract Protective antigen (PA) ofBacillus anthracis is being considered as a vaccine candidate against anthrax and its production has been explored in several heterologous host systems. Since the systems tested introduced adverse issues such as inclusion body formation and endotoxin contamination, the production fromB. anthracis is considered as a preferred method. The present study examines the effect of PA expression on the metabolism ofB. anthraci s producing strain, BH500, by comparing it with a control strain carrying an empty plasmid. The strains were grown in a bioreactor and RNA-seq analysis of the producing and non-producing strain was conducted. Among the observed differences, the strain expressing rPA had increased transcription ofsigL, the gene encoding RNA polymerase σ54, sigB, the general stress transcription factor gene and its regulatorsrsbW and rsbV, as well as the global regulatory repressorctsR . There were also decreased expression of intracellular heat stress related genes such asgroL, groES, hslO, dnaJ, anddnaK and increased expression of extracellular chaperonscsaA andprsA2 . Also, major central metabolism genes belonging to TCA, glycolysis, PPP, and amino acids biosynthesis were up-regulated in the PA-producing strain during the lag phase and down-regulated in the log and late-log phases, which was associated with decreased specific growth rates. The information obtained from this study may guide genetic modification ofB. anthracis to improve PA production.